Improving Student Vocabulary Mastery Using Word Mapping Strategy - Satuna Indah Wardani (OKARA: Jurnal Bahasa dan Sastra, 2015)
Abstract: The purpose of this study was to find out whether the word mapping strategywas able to improve the students’ vocabulary mastery. The process of masteringis mainly affected by the worst thought of the vocational students who said that English as the most difficult subject to learn and was often tracked into boringcondition since theywere not involved in the process of learning. Thisstudy was conducted by using classroom action research in two cycles and each cycleconsisted of four meetings. The subject of the research was the third grade of Accounting Department at State Vocational School 1 Pamekasan whichconsisted of 34 students. The research was carried out for one month.Theinstruments used to obtained primary data and the secondary data were vocabulary test, the students’ observation sheets, and questionnaire of the respondent.The result of test in preliminary until the test in cycle two showed that there was the improvement of the number of students who passed the test. Hopefully, this outcome will certainly be useful for both teachers and students in which its harmony will give the progress for learning English,especially vocabulary mastery.